Surviving the Doctoral Years - Kerlin, Scott P. (Education Policy Analysis Archives, 1995)
This article probes the implications of neo-conservative public education policies for the future of the academic profession through a detailed examination of critical issues shaping contemporary doctoral education in U.S. and Canadian universities. Institutional and social factors such as financial retrenchment, declining support for affirmative action, downward economic mobility, a weak academic labor market for tenure-track faculty, professional ethics in graduate education, and backlash against women's progress form the backdrop for analysis of the author's survey of current doctoral students' opinions about funding, support, the job market, and quality of learning experiences.